Interstellar scintillation, AGN physics and the SKA - Bignall, Hayley; Lovell, J; Rickett, B.J.; Macquart, Jean-Pierre; Jauncey, J.; Kedziora-Chudczer, L.; Ojha, Roopesh; Pursimo, T.; Senkbeil, C.; Shabala, S.; Dutka, M. (Australian Institute of Physics AIP, 2008)
A large fraction of compact, extragalactic radio sources exhibit rapid variability at centimetre wavelengths as their radio emission is scattered by electron density fluctuations in the interstellar medium of the Galaxy. Next-generation wide-field radio telescopes will have to account for this in forming deep images of the radio sky. Interstellar scintillation offers a unique probe of very small-scale structure in both the ionized interstellar medium and the compact jets of the radio sources themselves. The effective resolution is two orders of magnitude higher than achievable with very long baseline interferometry. The recent Micro-Arcsecond Scintillation-Induced Variability Survey revealed a reduction in ISS at 4.9 GHz with increasing source redshift, implying either an increase in the apparent angular size of high-redshift radio cores beyond that expected due to a cosmological decrease in brightness, or a decrease in the microarcsecond-scale core dominance towards high redshift. The result could be due either to source-intrinsic evolution in the selected sample, or to scatter-broadening in the intergalactic medium.